The family emotional system : an integrative concept for theory, science, and practice - Noone, Robert J.; Papero, Daniel V. (Lexington Books, 2015)
Presents an ongoing dialog among scientists, family investigators, and clinicians related to a natural systems view of the family and human behavior that has been occurring over several decades. This book explains how the family system can serve as an integrative framework within specific factual discoveries and hypotheses from many areas of science can be brought together and understood as various manifestations of a coherent whole. This work provides understanding of what is entailed in conceptualizing the family as an emotional system, a sense of the breadth and depth of knowledge the sciences are contributing to this effort, and examples of how this theoretical framework contributes to family research and practice.